Specifics of Criminal (Civil) Liability for Economic Offenses - Oleksii KHOVPUN; Artur ZAMRYHA; Victoria PANCHENKO; Valerii MASHYKA; Mykolai GERASYMENKО (Revista Jurídica Portucalense, 2023)
The paper considers a different understanding of criminal offenses that arise from economic offenses. The authors note that, in general, economic relations do not generate criminal law relations. All crimes and punishments are derivative, related to criminal consequences in economic relations. The authors consider extortion as a derivative of financial misconduct and define it as a component of the criminal process resulting from economic offenses. The authors consider the definition "extortion", its criminal component and its general place in the criminal law structure. It is determined that extortion should be considered as not only a criminal punishment, but also an involuntary act that can be implemented in the system of economic relations. It was determined that extortion was preventive in relation to other illegal norms in economic relations. The article shows that the prevention of extortion is determined not only by sufficient elaboration of certain types of economic relations, but also by the structure of counteraction at the level of legislative prohibitions. The paper defines the place of extortion in the system of criminal law relations and forms the principles of response.